1999
DOI: 10.1136/jms.6.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 31 CFTR mutations by polymerase chain reaction/oligonucleotide ligation assay in a pilot screening of 4476 newborns for cystic fibrosis

Abstract: Objectives-Molecular biological testing for genetic diseases has grown rapidly, but speed, accuracy, specificity, sensitivity, throughput, and cost become more important as large scale screening is considered. This is a pilot study of an assay for the simultaneous detection of up to 31 cystic fibrosis mutations in a multicentre population based screening of 4476 Italian newborns. Conclusions-PCR/OLA is a robust, accurate, user friendly method for cystic fibrosis screening of newborns using blood spots in a sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Other seven mutations, frequently observed in Italian CF patients (Q552X; 711+5G4A; 2790-2A4G; S589N; T338I; 1898+3A4G, and 1717-8G4A), were examined by sequencing. Using both methods in the general population from the same geographical area (San Giovanni Rotondo) in which our study was performed, Gasparini et al 23 found a carrier frequency of CFTR mutations of 3.22%. The CFTR polymorphic intron 8 polyT region was analyzed according to the method described by Chillon et al 24 This sequence contains five, seven, or nine thymidines (5T, 7T, 9T, respectively).…”
Section: Mutation Screening Of the Cftr Genementioning
confidence: 94%
“…Other seven mutations, frequently observed in Italian CF patients (Q552X; 711+5G4A; 2790-2A4G; S589N; T338I; 1898+3A4G, and 1717-8G4A), were examined by sequencing. Using both methods in the general population from the same geographical area (San Giovanni Rotondo) in which our study was performed, Gasparini et al 23 found a carrier frequency of CFTR mutations of 3.22%. The CFTR polymorphic intron 8 polyT region was analyzed according to the method described by Chillon et al 24 This sequence contains five, seven, or nine thymidines (5T, 7T, 9T, respectively).…”
Section: Mutation Screening Of the Cftr Genementioning
confidence: 94%
“…Genetic analysis was initially performed by PCR and oligonucleotide ligation assay (OLA) [10], then an extended analysis of the CFTR gene was performed using denaturing gradient gel electrophoresis (DGGE) analysis and sequencing as previously reported [1]. An allele-specific PCR assay was used to distinguish the 5T, 7T and 9T alleles.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 2, the frequency of ⌬F508 did not significantly differ between UC patients and controls, and was comparable to that expected for a general population from Italy (2.1%). 28 On the contrary, this mutation was underrepresented in the CD group, where it occurred at a 8-fold lower frequency compared with controls (P ϭ 0.021). Accordingly, heterozygous carriers had an estimated 88% reduced risk of developing CD in this population (OR ϭ 0.12).…”
Section: Resultsmentioning
confidence: 91%